Structural, Optical and Microhardness Properties of Lanthanum Doped Single Crystals of L-Alanine Acetate - GNANASEKARAN†, P.; MADHAVAN*, J. (Asian Journal of Chemistry, 2009)
Single crystals of pure and lanthanum doped L-alanine acetate were grown successfully by slow evaporation technique. The grown crystals were confirmed by X-ray powder diffraction studies. The pure and doped crystals were characterized by Fourier transform infrared (FT-IR) and UVVis- NIR studies. It was found that the optical properties wereenhanced by the incorporation of the dopant. Hardness studies were also carried out for the grown crystals. Non-linear optical studies reveal that the dopant has increased the efficiency of the L-alanine acetate crystal.